Acquired Thoracic Fistulas. Issue 4 (July 2021) - Layyous, Nadera; Yen, Andrew; Chaturvedi, Abhishek; Okamoto, Kanenori; Padwal, Jennifer A.; Abraham, Peter; Brouha, Sharon S.
Abstract : Fistulas are abnormal connections between 2 epithelial-lined structures. Thoracic fistulas may result from nonanatomic communications between spaces within the thorax, such as the lung, tracheobronchial tree, pleural space, and mediastinal structures, or between thoracic spaces and extrathoracic structures, such as the gastrointestinal tract. Furthermore, thoracic fistulas may result in communication between thoracic spaces and the spine or vascular structures. Potential causes include trauma, infection, neoplasm, surgical intervention, or medical syndromes. In this article, we discuss various acquired thoracic fistulas and their potential causes, key multimodality imaging manifestations, and clinical significance.